Elucidating π–π interaction-induced extension effect in sandwich phthalocyaninato compounds. Issue 1 (2nd January 2020) - Chen, Xin; Qi, Dongdong; Liu, Chao; Wang, Hailong; Xie, Zheng; Chen, Tse-Wei; Chen, Shen-Ming; Tseng, Tien-Wen; Jiang, Jianzhuang
Abstract : π–π interaction-linked extension in the perpendicular direction to the monomers and corresponding effect on nonlinear optic properties have been clearly disclosed over the multiple-decker sandwich-type phthalocyaninato metal compounds. Abstract : Electrochemical and theoretical investigations over triple-quadruple-, quintuple-, and sextuple-decker sandwich-type compounds [(Pc*)Sm][(Pc*)Cd n (Pc*) n ][Sm(Pc*)] ( n = 0–3) elucidate successive π–π interaction-linked extension in the perpendicular direction of the phthalocyanine plane along with increasing the stacked tetrapyrrole number, significantly improving the nonlinear optical properties including effective imaginary third order molecular hyperpolarizability and optical limiting threshold.